2017
DOI: 10.1007/s00484-017-1482-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MODIS-derived indices (2001–2013) to drought across Taiwan’s forests

Abstract: Tropical and subtropical ecosystems, the largest terrestrial carbon pools, are very susceptible to the variability of seasonal precipitation. However, the assessment of drought conditions in these regions is often overlooked due to the preconceived notion of the presence of high humidity. Drought indices derived from remotely sensed imagery have been commonly used for large-scale monitoring, but feasibility of drought assessment may vary across regions due to climate regimes and local biophysical conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…The soil micro and macro nutrients level can significantly affect species richness and communities Byrne et al (2017) examined plant's responses against precipitational change and concluded comparatively high level sensitivity. Chang et al (2018) and Skagen et al (2018) emphasized forest sensitivity and responses against precipitation variation in ecotones over a time scale.…”
Section: Introductionmentioning
confidence: 99%
“…The soil micro and macro nutrients level can significantly affect species richness and communities Byrne et al (2017) examined plant's responses against precipitational change and concluded comparatively high level sensitivity. Chang et al (2018) and Skagen et al (2018) emphasized forest sensitivity and responses against precipitation variation in ecotones over a time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Annual anomalies of precipitation and temperature of the overlapping time period , defined as the difference between the long-term mean and each year, were calculated. We also calculated the Standardized Precipitation Index (SPI) (Hirschi et al 2011) using the SPI Generator (University of Nebraska-Lincoln, NE, USA) to assess the interannual meteorological drought (Zou et al 2020) solely using monthly precipitation data (for details, see Chang et al (2018)). The SPI may be formed at different temporal resolutions (e.g., three months [SPI-3] to highlight seasonal variation) (Ji and Peters 2003); we derived the SPI-6 specifically for the distinct wet (May-October) and dry (November-April) seasons.…”
Section: Climate Datamentioning
confidence: 99%
“…Taiwan, a humid subtropical mountainous island with high annual precipitation (MAP) approximate 2500 mm year −1 , has experienced an amplifying seasonal rainfall and droughts (i.e., drier winter-spring and wetter summer), and regional discrepancies between wetter northern Taiwan and drier southern Taiwan over the past century [52,53]. Studies have demonstrated that the El Niño events during the preceding winter (November-February) will bring abundant rainfall for the following spring and summer seasons in Taiwan, and vice versa for La Niña events [54,55].…”
Section: Introductionmentioning
confidence: 99%